Study guides

☆☆

Q: What 4x y14 and 2x y8 solve using substitution?

Write your answer...

Submit

Still have questions?

Related questions

y=2x+9 and y=x+6

3(5x-2y)=18 5/2x-y=-1

2x-y=3 2/3x-y=-1

Solve this system of equation using substitution 2x plus 6y equals 24 and 3x-2x equals 24 ?Improved Answer:2x+6y = 243x-2x = 24 => x =24Substitute the value of x into the top equation to find the value of y:48+6y = 246y = 24-486y = -24y = -4So: x = 24 and y = -4

To solve the following equation by substitution, we need to have the equal sign. This will help us group the knowns and the unknowns.

When using substitution the answer to y0.5x plus 2 -y-2x plus 4 is y = -2 (x-1.

Use the substitution method to solve the system of equations. Enter your answer as an ordered pair.y = 2x + 5 x = 1

what is the solution of x-5y=10 and 2x-10y=20

If: x+y = 4 and y = 2x+1 Then: 4-x = 2x+1 => 3 = 3x => 1 = x So by substitution: x = 1 and y = 3

y = 4x - 8 y = 2x + 10 The substitution means to: Find the intersection point of their graphs, which is the common solution of this linear system of equations: 4x - 8 = 2x + 10 2x = 18 x = 9 y = 4(9) - 8 = 36 - 8 = 28 or y = 2(9) + 10 = 28 Thus the solution is (9, 28)

To solve a system of equations using substitution you solve one of the equations for one of the variables then substitute that into the other equation to solve for the other variable. For example. y = 6x 2x + 3y = -20 The first equation has already been solved for y. So, you simply substitute that into the second equation. 2x + 3(6x) = -20 2x + 18x = -20 20x = -20 x = -20/20 = -1 Now you have solved for x. You can substitute your answer for x back into the first equation to solve for y. y = 6x = 6(-1) = -6 Putting it all together... x = -1 y = -6

2x+7y=29 x=37-8y

People also asked